Development of a children’s humorous audio podcast integrating the seven habits of great indonesian children to strengthen character education in primary schools - Yuriananta, Renda; Angga Rini, Titis; Oktarianto, M. Luthfi; Wibowo, Sigit; Prakoso, Hikmal Tegus Budi; Wahani, Pradela Maynafia (Universitas Kanjuruhan Malang, 2026)
This study aimed to develop a humorous children’s audio podcast based on the Seven Habits of Great Indonesian Children to strengthen character education in elementary schools. Using a Research and Development design with the ADDIE model, data were collected through observations, interviews, expert validation, student questionnaires, and short character-based tests. Instruments included validation sheets, teacher practicality questionnaires, student response forms, and tests aligned with the Seven Habits indicators. Data were analyzed using descriptive quantitative techniques supported by qualitative feedback. The product consisted of seven humorous podcast episodes. Validation results indicated high feasibility (mean = 4.67). Field testing with 48 students at SDN Sumberdem 1, Malang Regency, showed very positive responses (mean = 4.74; 95%). Students were enthusiastic, understood moral messages clearly, and demonstrated emerging positive traits such as empathy, responsibility, discipline, and motivation. The podcast is feasible, engaging, and effective for strengthening character education and supporting the Pancasila Student Profile.